2006
DOI: 10.1080/15572536.2006.11832614
|View full text |Cite
|
Sign up to set email alerts
|

Dating divergences in the Fungal Tree of Life: review and new analyses

Abstract: The collection of papers in this issue of Mycologia documents considerable improvements in taxon sampling and phylogenetic resolution regarding the Fungal Tree of Life. The new data will stimulate new attempts to date divergences and correlate events in fungal evolution with those of other organisms. Here, we review the history of dating fungal divergences by nucleic acid variation and then use a dataset of 50 genes for 25 selected fungi, plants and animals to investigate divergence times in kingdom Fungi. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
282
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(297 citation statements)
references
References 35 publications
14
282
1
Order By: Relevance
“…S3A). Although several inversions occurred within syntenic blocks, the overall synteny can be traced before separation of the orders Eurotiales and Onygenales, dated between 150 and 400 Mya depending on molecular clock calibration (19). Members of other rvt lineages exhibit similar degrees of synteny ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…S3A). Although several inversions occurred within syntenic blocks, the overall synteny can be traced before separation of the orders Eurotiales and Onygenales, dated between 150 and 400 Mya depending on molecular clock calibration (19). Members of other rvt lineages exhibit similar degrees of synteny ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The phylogenetic position of U. virens was evaluated among other eleven selected fungal species (10 ascomycota and one basidiomycota outgroup) using a set of highly conserved singlecopy genes suggested for the Fungal Tree of Life 28 (Supplementary Table 10, Supplementary Note 5). The analysis revealed that U. virens is more closely related to two entomopathogenic Metarhizium spp.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic distribution of mtTyrRSs with structural adaptations required for group I intron splicing activity in CYT-18 suggests that this activity was acquired by Pezizomycotina mtTyrRSs during or after the divergence of this fungal subphylum from Saccharomycotina, 350-600 million years ago (22). The driving force was presumably the need to compensate for structural defects acquired by group I introns that had inserted as mobile elements into essential mtDNA genes.…”
Section: Identification Of Functionally Important Amino Acids By Sequmentioning
confidence: 99%